2015
DOI: 10.1186/s12958-015-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine administration of human chorionic gonadotropin does not improve pregnancy and life birth rates independently of blastocyst quality: a randomised prospective study

Abstract: BackgroundSuccessful embryo implantation depends on a well-timed maternal-embryonic crosstalk. Human chorionic gonadotropin (hCG) secreted by the embryo is known to play a key role in this process and to trigger a complex signal transduction cascade allowing the apposition, attachment, and invasion of the embryo into the decidualized uterus. Production of hCG was reported to be dependent on blastocyst quality and several articles suggested that intrauterine hCG injection increases pregnancy and implantation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 37 publications
1
57
1
Order By: Relevance
“…A study conducted by Wirleitner et al in 2015 showed that intrauterine HCG injection prior to ET does not improve the pregnancy and live birth rates independently of blastocyst quality. Furthermore hCG's effect on live birth rate (LBR) was similar between women over the age of 38 and under the age of 38 (7). These three studies used blastocyst.…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted by Wirleitner et al in 2015 showed that intrauterine HCG injection prior to ET does not improve the pregnancy and live birth rates independently of blastocyst quality. Furthermore hCG's effect on live birth rate (LBR) was similar between women over the age of 38 and under the age of 38 (7). These three studies used blastocyst.…”
Section: Discussionmentioning
confidence: 97%
“…Live birth rate Three studies (Aaleyasin et al, 2015;Mansour et al, 2011;Wirleitner et al, 2015) reported LBR. Pooling the results of the three studies (n = 2164) showed no significant difference between the group who received intrauterine HCG and the control group (RR 1.13; 95% CI 0.84 to 1.53) (Figure 4).…”
Section: Primary Outcome Measurementioning
confidence: 99%
“…Five studies (Aaleyasin et al, 2015;Hong et al, 2014;Mansour et al, 2011;Wirleitner et al, 2015;Zarei et al, 2014) reported spontaneous abortion rate. No significant heterogeneity was found between the studies (I 2 = 0%); therefore, a fixed effects model was used.…”
Section: Spontaneous Abortion Ratementioning
confidence: 99%
See 2 more Smart Citations